Agresividad y práctica de valores en estudiantes de la institución Educativa Primaria N° 60080 Patricio Olórtegui Saenz, Caballo Cocha Ramón Castilla 2023 - Del Aguila Malafaya, Elizabeth (2024)
The present study was carried out with students from the primary educational institution N° 60080 Patricio Olórtegui Sáenz, Caballo cocha Ramón Castilla 2023, with the main objective of examining the relationship between aggressiveness and the practice of values in this demographic group. The methodology employed was based on a relational approach, with a field research design that was both cross-sectional and bivariate. The study population consisted of 758 students, from which a sample of 176 was selected. These students were observed and surveyed using validated data collection instruments. The results obtained revealed a significant relationship between childhood aggressiveness and the practice of values among the analyzed students. It was observed that among those with moderate levels of aggressiveness, there was a higher percentage of high-value practice (12.4%) compared to those with moderate levels (8.1%). In contrast, students with high levels of aggressiveness exhibited a higher proportion of moderate-value practice (91.3%) compared to high-value practice (87.6%). In conclusion, divergent patterns in the relationship between childhood aggressiveness and the practice of values were evident among primary school students. The higher proportion of value practice among moderately aggressive individuals suggests a significant ability to adhere to positive values, even in the presence of aggressiveness levels. Conversely, the predominance of moderate-value practice among highly aggressive students suggests difficulties in maintaining behavior based on values.